2018
DOI: 10.1111/jwas.12569
|View full text |Cite
|
Sign up to set email alerts
|

Dietary protein requirement for juvenile mandarin fish, Siniperca scherzeri

Abstract: An 8‐week feeding trial was conducted to investigate the dietary protein requirement of juvenile mandarin fish, Siniperca scherzeri, a demersal freshwater piscivore with high commercial value in East Asia. Five isolipidic (100 g/kg) and isoenergetic (20 MJ/kg) practical diets were formulated to contain graded levels of 450, 500, 550, 600, and 650 g/kg crude protein, using mackerel fishmeal as the sole source of protein. Each of the five test diets was fed to visual satiety to triplicate groups of fish (initial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 16 publications
1
8
0
Order By: Relevance
“…2 HSI (%) = 100 × (weight of liver/weight of fish). 3 VSI (%) = 100 × (weight of viscera/weight of fish)]. 4 CVBL (%) i = 100 × (standard deviation of initial length of fish/mean initial length of fish).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…2 HSI (%) = 100 × (weight of liver/weight of fish). 3 VSI (%) = 100 × (weight of viscera/weight of fish)]. 4 CVBL (%) i = 100 × (standard deviation of initial length of fish/mean initial length of fish).…”
Section: Resultsmentioning
confidence: 99%
“…In Korea, China, and Vietnam, fish of the genus Siniperca [1,2] are commercially valuable because the meat is palatable [1][2][3][4]. However, they are challenging to farm with formulated fish feed due to their strong preference for live prey [5,6], and thus the commercial supply of S. scherzeri is limited [4,7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike the mammals, protein is mostly used for energy consumption and tissue deposition in fish (Ogino & Saito, 1970). Numerous studies have reported that fish fed low protein diets caused a decrease in growth performance, digestive and absorptive ability, and body protein composition (Einen & Roem, 1997; Jiang et al, 2016; Sankian, Khosravi, Kim, & Lee, 2019). On the contrary, an optimal protein level could improve the growth and maintain the normal physiological metabolism in fish.…”
Section: Introductionmentioning
confidence: 99%
“…The growing interest in mandarin fish culture has been triggered by increasing demand on its shrinking wild stock (Wu et al 1997;Chu et al 2013). Yet, so far, there is relatively little scientific information available concerning mandarin fish nutrition (Zhang et al 2009;Lee et al 2012;Sankian et al 2017Sankian et al , 2018Sankian et al , 2019, and its commercial production still relies on expensive live prey. Hence, one of the most important steps in developing and implementing a profitable and sustainable culture practice for this species is to formulate a nutritionally balanced and cost-effective commercial feed.…”
Section: Introductionmentioning
confidence: 99%